KEHIDUPAN SOSIAL EKONOMI PENGRAJIN BATU AKIK DI NAGARI SIKABAU KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA (2004-2012) - Rizal, Andoni; Hardi, Etmi; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
Agate processing business run society in Nagari Sikabau a craft activity . Thought to open a business that is run agate handicraft artisans todays society is to follow the activities of the business which was run first residents doing business as craftsmen . This artisan activity is an activity that utilizes a natural potential types of rocks are processed into stone jewelery . The problem in this study are ; how the emergence of agate business and socio-economic life of agate craftsman in Nagari Sikabau district. Dharmasraya arbor Island during 2004-2012 .The results showed that the business of making people run agate artisans in Nagari Sikabau District of Arbor Island involving others in the business activities or status as a craftsman . Origin of capital to open a business of making businesses run agate artisan community comes from its own capital , and loans . The production process is carried out with the several stages namely ; 1) cutting process , 2) the process of pattern formation , 3) grinding process , and lastly 4) the process of refining and pelicinan done by using some sort of special chemicals that make the rocks slippery and shiny . Based on the research that has been done can be concluded that , agate processing businesses run craftsmen in Nagari Sikabau society , can make the conditions of social life is better in terms of economy. .